Solid state dewetting of polycrystalline Mo film on sapphire. (15th October 2017) - Kovalenko, O.; Szabó, S.; Klinger, L.; Rabkin, E.
Abstract: We studied the kinetics of solid state dewetting of a thin Mo film deposited on a sapphire substrate. The overall kinetics of the process can be described by the Johnson-Mehl-Avrami-Kolmogorov equation with two different exponents, indicating a decrease of the holes nucleation rate for the long annealing times. We related this decrease to the role of grain boundaries and triple junctions in the nucleation of holes, and the grain growth in the film during annealing. Every expanding hole was partially surrounded by the elevated, abnormally large grains, while the remaining part of the hole contacted an unperturbed film of the original thickness. The expansion of the holes occurred predominantly in the direction of the flat film. We formulated a kinetic model of hole expansion based on surface diffusion along the edge of a flat rim in the direction of an abnormal elevated grain. Graphical abstract: Image 1